Standardized ileal digestibility of amino acids in eight genotypes of barley fed to growing pigs. (25th May 2016) - Spindler, H. K.; Mosenthin, R.; Rosenfelder, P.; Jørgensen, H.; Bach Knudsen, K. E.; Sauer, N.; Htoo, J. K.; Eklund, M.
Abstract : To determine chemical composition, physical characteristics and standardized ileal digestibility (SID) of CP and amino acids (AA) in eight current hulled barley genotypes, an experiment with growing pigs has been conducted. These genotypes included Yool, Campanile, Lomerit, Travira, Anisette, Canberra, Metaxa and Fridericus. Growing barrows with an average initial BW of 30±2 kg were surgically fitted with simple T-cannulas at the distal ileum, and allotted to an 8×9 Youden square design with eight periods of 6 days each and nine pigs. Barley was the sole dietary source of CP and AA. On average, the eight genotypes contained on as-fed basis 10.7% CP, 15.2% total non-starch polysaccharides (NSP), 17.1% NDF and 4.1% β -glucan, and had a mean test weight (TW) of 72.2 kg/hl. The SID of CP in the barley genotypes varied from 69% to 74%, and was greater ( P <0.01) for genotypes Travira, Anisette and Metaxa compared to Yool and Campanile. Standardized ileal digestibility of Lys, Met and Trp ( P <0.05) but not of Thr differed between genotypes. Moreover, barley genotypes differed in their standardized ileal digestible content (cSID) of CP and AA. Furthermore, SID and cSID of CP and most AA linearly decreased ( P <0.05) with increasing NDF and total sugar content. Standardized ileal digestibility of CP and some AA and cSID of CP and most AA decreased linearly with increasing TW ( P <0.05). Additionally, SID and cSID of CP and AA of most barley genotypes were lower when compared to tabulated values. In conclusion, a comprehensive database on chemical composition and SID of CP and AA in eight current barley genotypes has been made available. However, as present SID values are lower compared to feed tables, adjustments are required to minimize the risk of overestimating the actual protein value of barley for pigs.